Exploring psycho-educational horizons in the face of the climate crisis: links between contemplative pedagogy and the eco-relational paradigm of peace. - Gonzalez Torres, Leonardo; Vázquez Rico, Inés (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
Starting from the analysis of the global ecological crisis and from the concept of interbeing, the practice of compassion and the approach of eco-pedagogy , this article explores psycho-educational perspectives for an ecological contemplative pedagogy that articulates critical , experiential and transformative practices . Through the analysis of experiences from the Círculo de estudios para la paz and IIPE 2024, the epistemological, political and affective challenges of the emerging eco -relational paradigm of peace are discussed . The work concludes by highlighting the need to integrate ancestral knowledge, contemplative practices, and an emotional reconnection with the earth to consolidate an education committed to ecological justice and planetary regeneration .